Posterior reversible encephalopathy syndrome in a patient with diabetic ketonuria - Sharma, Ishwor; Banjade, Prakash; Chellamuthu, Sasikumar Atthipalayam; Saeed, Faisal; Dallakoti, Prajut (Journal of Kathmandu Medical College, 2020)
Posterior reversible encephalopathy syndrome is a condition presenting with non-specific symptoms like nausea, vomiting and headache along with neurological manifestations like altered mental status, seizure, visual impairment and even coma. These symptoms are coupled with characteristic radiological findings of vasogenic edema in the bilateral parieto-occipital lobe which is usually reversible. We present here, a young 30 years old male, with dizziness, vomiting, generalized weakness, altered mental status with cortical blindness and focal and generalized tonic-clonic seizures in the background of first presentation of type 2 diabetes mellitus with ketonuria. Characteristic findings in Magnetic Resonance Imaging and reversal of the symptoms helped to reach the diagnosis of posterior reversible encephalopathy syndrome in our patient. The patient was discharged in stable condition after reversal of the symptoms and treatment of type 2 diabetes mellitus.